Flexible ureterorenoscopy for the treatment of lower pole calyx stones: influence of different lithotripsy probes and stone extraction tools on scope deflection and irrigation flow - Michel, Maurice Stephan; Knoll, Thomas; Ptashnyk, Taras; Köhrmann, Kai-Uwe; Alken, Peter (European urology, 2002)
The 7.5 and 9.0F flexible ureterorenoscopes are used widely in endourology. These scopes, along with new available tools and probes, enable intrarenal ureteroscopic access to renal stones in the lower pole. Following individual clinical experiences the infundibulopelvic angle has to be respected for the selection of different scopes, tools and probes. The aim of this study was to determine the influence of different scopes, tools and probes on the angle of the active and passive flexion of the flexible ureterorenoscope. The angles of the active and passive flexion and maximum irrigation flow of different flexible ureterorenoscope (9.0F Wolf, 7.5F Olympus, 7.5F Storz) were measured repeatedly in vitro using nine different inserted tools and/or probes. In addition, the maximum allowing for easy passage of the nine different tools/probes through the channel of the scope were measured. The Olympus scope without working instrument present, allows for the greatest deflection. The flexible Lithoclast, the non-nitinol baskets, and the 365μm laser probes significantly inhibit the deflection of all scopes. The greatest deflection with inserted working tool was possible using the Wolf and Storz scopes. Both nitinol tools as well as the 200μm laser probe had only minimal influence on the deflection. The 200μm laser probe reduces the irrigation flow from 50 to 28ml/min. In contrast, the baskets reduce the irrigation flow from 50 to 2ml/min. There are significant differences of the active and passive flexion depending on the ureterorenoscopes itself and the different tools. In order to perform a successful flexible ureterorenoscopic stone treatment in the lower pole, the inhibition of the flexion of the different scopes together with the individual infundibulopelvic angle must be respected when selecting different tools and probes.